Bioactive Protein Produced By Lactobacillus Plantarum ATCC 8014 In The Presence Of Allium Sativum - lsmatul Nurul Asyikin lsmail; Hairul Shahril Muhamad; Abdul Jalil Abdul Kader; Rosfarizan Mohamed; Hanina Mohd Noor; Salina Mat Radzi; Maryam Mohamed Rehan (2024)
Several studies have reported that sub inhibitory concentrations of antibiotics or antimicrobials are capable to modulate bacteria transcription processes. Therefore, the bacteria might have introduced new proteins in mild stress surroundings like in the presence of antimicrobial agents at low concentrations. However, there are limited elucidations about unexpected ability of natural antimicrobial compounds to become a signaling agent capable to induce biological functions in bacteria at low concentrations. Thus, this present study aims to e'xplore the proteins production by Lactobacillus plantarum ATCC 8014 in the presence of Allium sativum at sub-minimal inhibitory concentration (sub-MIC). The Minimum Inhibition Concentration (MIC) of A. sativum against L. plantarum was 33.33% from microdilution assay. L. plantarum cells were treated with A. sativum at sub-MIC (0.05 x MIC) in the fermentation process. Three new protein bands (approximate size of 97.83 kD, 53.56 kD and 46.71 kD) were detected by SDS-PAGE profile for the treated bacteria. LC-MSIMS analysis identified 11 possible proteins from the three protein bands expressed in mild stress condition. The proteins showed antimicrobial activity toward several Gram-positive and I Gram-negative bacteria. Hence, L. plantarum ATCC 8014 in mild stress condition with the presence of 0.05 x MIC A. sativum could regulate bioactive proteins production.